2020
DOI: 10.3389/fmicb.2020.595622
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Citric Acid and Malic Acid on Fermentation Quality and Bacterial Community of Cassava Foliage Silage

Abstract: The microbiota and fermentation quality of cassava foliage (CF) ensiled in the absence of additive (CK), or the presence of citric acid (CA), malic acid (MA), and their combination with a Lactobacillus plantarum strain (CAL and MAL)were investigated. These additives reduced (P < 0.05) the pH, butyric acid, and ammonia-N contents but increased (P < 0.05) the lactic acid content, and CAL and MAL showed similar remarkable effects. Paenibacillus (mean, 27.81%) and Bacillus (mean, 16.04%) were the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
3
23
1
Order By: Relevance
“…Bacillus , a type of facultatively anaerobic and Gram-positive bacteria, can secrete bacteriocin and inhibit the activities of undesirable bacteria. In addition, some species of Bacillus can produce LA ( Li M. et al, 2020 ). Weissella , a type of heterofermentative LAB, converts 1 mol glucose to 1 mol AA, 1 mol LA, and 1 mol CO 2 ( Wang M. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus , a type of facultatively anaerobic and Gram-positive bacteria, can secrete bacteriocin and inhibit the activities of undesirable bacteria. In addition, some species of Bacillus can produce LA ( Li M. et al, 2020 ). Weissella , a type of heterofermentative LAB, converts 1 mol glucose to 1 mol AA, 1 mol LA, and 1 mol CO 2 ( Wang M. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Malic acid has antioxidant and antibacterial functions and is widely used in food, pharmaceutical, healthcare, cosmetics, and other industries. Moreover, malic acid, which can be used as a carbohydrate source, provides energy for LAB and accelerates LAB growth ( Li M. et al, 2020 ). Notably, the relative abundance of differential pathways caused by glucose was lower compared with those of pathways caused by malic acid, cellulase, and B. subtilis .…”
Section: Discussionmentioning
confidence: 99%
“…Within silage, Paenibacillus species (spore-forming bacteria) could enhance growth of LAB, tolerate acidic conditions and produce bacteriocins that inhibit yeast and molds ( Xu et al, 2018 ; Singh et al, 2019 ). However, it is important to note that in some cases Paenibacillus can compete with LAB for fermentable sugars, limiting its growth ( Li et al, 2020 ). In addition, they have a vast lignocellulolytic potential that may improve the digestion of complex carbohydrates in the bovine rumen ( Ticona et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of FAE was not detected within the reconstructed MAGs. Interestingly, Cellulosimicrobium and Paenibacillus species have been cataloged as desirable microorganisms in cassava foliage silage ( Li et al, 2020 ). Finally, this study reported the design and characterization of a mixed consortium, obtained from the M. maximus phyllosphere, composed of LAB and LB.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial count of each sample was determined by the method of Cai et al (1999) , and described by Li et al (2020) . In brief, each sample of 10 g was mixed with 90 ml sterile saline, shaken for 30 min and then filtered through sterile gauze.…”
Section: Methodsmentioning
confidence: 99%